1992
DOI: 10.1007/bf00027163
|View full text |Cite
|
Sign up to set email alerts
|

Translation controls the expression level of a chimaeric reporter gene

Abstract: Transcriptional and translational fusions between the reading frame of the beta-D-glucuronidase gene (gusA) and the 2' as well as the 1' promoter of mannopine synthase (mas), a TR locus of Agrobacterium tumefaciens, were made. The expression of these constructs was studied in the transgenic F1 offspring of independent tobacco transformants at the protein level by assaying for GUS activity and western blot analysis of the GUS protein and at the steady-state mRNA level. In leaves, stems and roots no correlation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 56 publications
(63 reference statements)
1
46
0
Order By: Relevance
“…This may not be true in all cases (e.g. Hensgens et al, 1992). In the present study we made 'the assumption that these parameters were similar in the green and white mesophyll cells of control and immutans leaves, and that they did not vary appreciably as a function of cell size.…”
Section: Lhcb Transcription Is Coordinated With Cell Size and Chloropmentioning
confidence: 81%
“…This may not be true in all cases (e.g. Hensgens et al, 1992). In the present study we made 'the assumption that these parameters were similar in the green and white mesophyll cells of control and immutans leaves, and that they did not vary appreciably as a function of cell size.…”
Section: Lhcb Transcription Is Coordinated With Cell Size and Chloropmentioning
confidence: 81%
“…For example, it has been shown that there was no correlation between the steady-state level of GUS mRNA and enzyme activity in transgenic plants. 28) In this case, the translation of GUS mRNA and the stability of the GUS protein played crucial roles in determining the ultimate level of GUS activity. Furthermore, the herbicide (glyphosate [N-(phosphonomethyl) glycine])-resistant cell culture of Corydalis semperviren had a 30-to 40-fold higher level of the herbicide target enzyme, 5-enolpyruvylshikimate-3-phosphate synthase (EPSPS), with a 10-fold enhanced level of the corresponding mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…The available evidence suggests that there are unique and overlapping sets of mRNAs among different plant organs (Kamalay and Goldberg, 1980;Kamalay and Goldberg, 1984). For the most part it is thought that a given population of mRNAs provides a template that is instrumental in determining the form and function of each cell in the plant body, however, if translational or post-translational regulation is important, this may not always be the case (Hensgens et al, 1992). The study of tissue-and cell-type preferential mRNA accumulation is a means to elucidate the genetic and molecular basis of plant development and function.…”
Section: Organ-preferential Mrna Accumulationmentioning
confidence: 99%